2004
DOI: 10.1002/jbm.b.30149
|View full text |Cite
|
Sign up to set email alerts
|

Elemental distributions and microtensile bond strength of the adhesive interface to normal and caries‐affected dentin

Abstract: The aim of this study was to evaluate the microtensile bond strength (microTBS) and the elemental contents of the adhesive interface created to normal versus caries-affected dentin. Extracted human molars with coronal carious lesions were used in this study. A self-etching primer/adhesive system (Clearfil Protect Bond) was applied to flat dentin surfaces with normal and caries-affected dentin according to the manufacturer's instructions. After 24 h water storage, the bonded specimens were cross-sectioned and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
0
11

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 63 publications
3
64
0
11
Order By: Relevance
“…Interestingly, during the caries-forming process, the tubules become obliterated with whitlockites, thus reducing permeability of the caries-affected dentin. 15 In general, SEM analysis revealed a thicker hybrid layer formation for the Single Bond groups compared to the Adper Prompt L Pop groups. This is most likely due to the specific feature of each adhesive system, one being an "etch and rinse" system that uses an aggressive phosphoric acid etching and the other a self-etching adhesive that is less aggressive.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Interestingly, during the caries-forming process, the tubules become obliterated with whitlockites, thus reducing permeability of the caries-affected dentin. 15 In general, SEM analysis revealed a thicker hybrid layer formation for the Single Bond groups compared to the Adper Prompt L Pop groups. This is most likely due to the specific feature of each adhesive system, one being an "etch and rinse" system that uses an aggressive phosphoric acid etching and the other a self-etching adhesive that is less aggressive.…”
Section: Discussionmentioning
confidence: 91%
“…The hybrid layers of both Single Bond and Adper Prompt L Pop for the caries-affected dentin were thicker than those formed in normal dentin, an observation which was also previously reported. 9,15 This phenomenon may be due to the partially demineralized nature of intertubular dentin in caries-affected dentin, which permits deeper acid demineralization and deeper monomer infiltration compared to normal dentin.…”
Section: Discussionmentioning
confidence: 99%
“…There are differences in modulus of elasticity and hardness between bonded CAD and bonded sound dentin in primary teeth 27) . The physical and chemical properties of sound dentin are unlike from those of CAD 28) . The latter is more porous and softer than sound dentin due to partial demineralization, with narrow and obliterated dentinal tubules due to deposition of intratubular dentin and with a hybrid layer thicker than that of sound dentin 18) .…”
Section: Discussionmentioning
confidence: 96%
“…The affected layer is generally not removed during treatment [10][11][12] . Therefore, following caries removal and cavity preparation for an adhesive restoration, a large area of the cavity floor is composed of cariesaffected dentin 13) . The physical and chemical characteristics of caries-affected dentin are very different from those of normal dentin.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, most tubules of caries-affected dentin are occluded with mineral deposits 15,16) . Electron probe microanalysis also showed that elemental contents are different between normal and caries-affected dentin surfaces 13) . With due consideration of these differences, they may have significant implications for temperature rise between normal and caries-affected dentin.…”
Section: Introductionmentioning
confidence: 99%